Evaluation of child development: beyond the neuromotor aspect - Sophie Helena Eickmann; Alan Martin Emond; Marilia Lima (Brazilian Society of Pediatrics, 2016)
Objective: To review the epidemiology and update the scientific knowledge on the problems of development and behavior in childhood, and the recommendations for the role of the pediatrician in identifying and managing delays and disturbances in child development and mental health. Sources: A search for relevant literature was performed in the PubMed and Scopus databases and publications of the National Scientific Council on the Developing Child. Summary of the findings: With the decline in the incidence of communicable diseases in children, problems with development, behavior, and emotional regulation are increasingly becoming a part of the work of pediatricians, yet many are not trained and feel uncomfortable about this extension of their role. The available screening tools for child development and behavior are reviewed, and a "school readiness" checklist is presented, together with recommendations on how the pediatrician can incorporate developmental surveillance into routine practice, aware of the need for children to acquire social, emotional, and cognitive skills so that they can develop their full potential. Conclusions: The pediatrician's role in the future will include both physical and mental health, recognizing that social development, resilience, and emotional maturity are as important as physical growth and neuromotor skills in a child's life course.